Videotorakoskopie a videoasistované chirurgické výkony u penetrujících poranĕní hrudníku - Demes, R; Cermák, S; Výborný, J; Pesková, M; Zeman, M; Krska, Z; Rehák, M; Trca, S; Paul, O (Rozhledy v chirurgii, 2001)
Diagnosis and treatment of the penetrating injury of the chest is quite difficult. In all types/sizes of hospitals/these injuries has to be immediately treated in surgery departments. Often decision about the optimal treatment of these injuries is quite difficult. In this paper experience with 37 cases of penetrated trauma is presented. Authors defined adequate criteria for selection of the chest tube, videothoracoscopy, video-assisted thoracic surgery (VATS), emergency thoracotomy and thoracophrenolaparotomy.
Keywords: Thoracoscopy; Wounds, Gunshot; torakoskopie; střelné rány; Female; Thoracic Injuries; lidé; Adult; Thoracic Surgery, Video-Assisted; Male; Humans; dospělí; ženské pohlaví; bodné rány; hrudní chirurgie video-asistovaná; Wounds, Stab; mužské pohlaví; poranění hrudníku